2003
DOI: 10.2135/cropsci2003.0995
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield and Persistence of Chicory and English Plantain

Abstract: ball et al., 1997). The ecology of natural populations of plantain and its biology as a weed have been investigated Graziers in the northeast USA often face forage shortages in mid- (Bassett, 1973; Kuiper and Bos, 1992). Apart from older summer. Chicory (Cichorium intybus L.) and English plantain (Plantago lanceolata L.) have been introduced in the USA as sumer-active reports in the scientific literature, the forage value of perennial herbs for pastures. We conducted two experiments at Rock plantain is relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 2 publications
5
50
0
3
Order By: Relevance
“…Conversely, while plantain is technically taprooted, its root system is more fibrous due to a greater number of adventitious roots compared to chicory (Sanderson et al. ). Therefore, as expected in experiment 1, chicory consistently had a greater root mass and taproot diameter than plantain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, while plantain is technically taprooted, its root system is more fibrous due to a greater number of adventitious roots compared to chicory (Sanderson et al. ). Therefore, as expected in experiment 1, chicory consistently had a greater root mass and taproot diameter than plantain.…”
Section: Discussionmentioning
confidence: 99%
“…In plantain, a 5‐week defoliation interval has been shown to produce greater shoot dry matter than a 3‐week defoliation interval (Sanderson et al. , Labreveux et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall in June 2001, however, was 1.7 inches greater than in 2000 and 1.4 inches greater than the long‐term average. The yields of Grasslands Puna, Forage Feast, and Lacerta were similar to those obtained in other field‐plot research at the same site (13). In that study, yields of the three forage chicory cultivars averaged 7100 lb/acre in 2000 and 4700 lb/acre in 2001.…”
Section: Forage Yieldsmentioning
confidence: 99%
“…By comparison, previous studies had shown that survival of Lancelot and Tonic plantain during the first winter following plant establishment can be relatively high but is often followed by an almost complete loss of plants after the second winter (Sanderson et al, 2003;Labreveux et al, 2004). This improved freezing tolerance occurred even when wintertime conditions resulted in only 9% plant mortality.…”
Section: Discussionmentioning
confidence: 72%
“…Sanderson et al (2003) also observed in one experiment that Lancelot had relatively good survival at 2 yr after establishment but that surviving plants were weak and contributed little to dry-matter yield. Sanderson et al (2003) also observed in one experiment that Lancelot had relatively good survival at 2 yr after establishment but that surviving plants were weak and contributed little to dry-matter yield.…”
Section: Discussionmentioning
confidence: 90%